ANALISIS KELAYAKAN FINANSIAL DAN NILAI TAMBAH AGROINDUSTRI SERAT SABUT KELAPA (COCO FIBER) DI KECAMATAN KATIBUNG KABUPATEN LAMPUNG SELATAN - Cipta Panji Utama; Sudarma Widjaya; Eka Kasymir (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2016)
The purposes of this research are to analyze the financial feasibility of cocofiber agrondustry, the added alue from processing in cocofiber agroindustry and the prospect of cocofiber agroindustry.  Cocofiber is fiber made from coconut shell.  This research was conducted in Katibung subdistric of South Lampung Regency. This research location was chosen purposively based on stablished and the new one agroindustry in Katibung Subdistric. The. The results of this research showed that the agroindustry of cocofiber were profitable and feasible to be developed, established agroindustry  makes an added value more than the new one agroindustry and  cocofiber agroindustry in Katibung district have a potential prospect views from financial, market, technique and social and environment aspects.Key words: addedvalue, agroindustry,cocofiber,feasibility